2019
DOI: 10.1089/nat.2018.0759
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical Exon Skipping Studies with 2′-O-Methyl Phosphorothioate Antisense Oligonucleotides in mdx and mdx-utrn−/− Mice Inspired by Clinical Trial Results

Abstract: Duchenne muscular dystrophy is a severe, progressive muscle-wasting disease that is caused by mutations that abolish the production of functional dystrophin protein. The exon skipping approach aims to restore the disrupted dystrophin reading frame, to allow the production of partially functional dystrophins, such as found in the less severe Becker muscular dystrophy. Exon skipping is achieved by antisense oligonucleotides (AONs). Several chemical modifications have been tested in nonclinical and clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Previous studies in mdx indicated that twice weekly SC administration of 100 mg/kg M23D gave rise to optimal tissue levels and exon skipping [24,25]. Therefore, this dosing regimen was the starting point of this study, including both an 10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in mdx indicated that twice weekly SC administration of 100 mg/kg M23D gave rise to optimal tissue levels and exon skipping [24,25]. Therefore, this dosing regimen was the starting point of this study, including both an 10).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the exon skip studies in mdx mice, including recent publications, have reported on AON-induced exon 23 skipping data assessed using nonquantitative, sometimes even nested, PCR with gel-based or densitometric assessment of exon skip levels [42][43][44][45]25]. A disadvantage of this approach is that it has the propensity to overestimate exon skip levels due to the PCR bias, favoring amplification of the smaller exon skip product over the exon 23-containing nonskipped amplicon, in particular, when using a large number of PCR cycles or nested PCR [46,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One clear advantage of AOs in exon skipping provides the basis for modeling, significantly enhancing its ability to be tailored with, thus improving delivery efficiency and exon skipping efficacy. In this review, 15 out of 23 studies have employed various constructs of different backbones comprising of either phosphorodiamidate morpholino oligomers (PMOs) ( Akpulat et al, 2018 ; Lee et al, 2018 ), 2′-O-methyl phosphorothioate (2OMePS) AO ( Van Putten et al, 2019 ), 2′-deoxy-2′-fluoro phosphorothioate (2FPS) AO ( Jirka et al, 2015 ), or 2′-O-methoxyethyl oligonucleotide (MOE) ( Yang et al, 2013 ). The results were encouraging, supporting the use of these constructs as possible alternatives.…”
Section: Resultsmentioning
confidence: 99%
“…However, one has to bear in mind that in most of these mouse studies the exon skipping and dystrophin restoration levels are much higher than observed in humans. Indeed, when restoring lower dystrophin levels in mdx models, functional effects are more modest [112][113][114]. Another consideration is that most mdx models regenerate extremely well.…”
Section: Expert Opinionmentioning
confidence: 99%